2021
DOI: 10.26907/esd.16.3.24
|View full text |Cite
|
Sign up to set email alerts
|

Using social networks for social upbringing

Abstract: The article addresses the potential of using social networks in social education and for solving the problems of youth socialization. There is an urgent social need for the harmonious development of the child's personality, including in the Internet environment. At the same time, there is insufficient knowledge about the organization of education in social networks in science. The article identifies the experience of successful interaction between teachers and students on the Internet and ways of organizing ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 4 publications
0
2
0
1
Order By: Relevance
“…Их не так много, как хотелось бы, но это статьи ведущих российских специалистов по воспитательной проблематике. Исследователи поднимают проблемы научно-методического обеспечения процесса воспитания в школе (Selivanova & Parfyonova, 2021), системного подхода к применению исследовательских методов в теории вопитания (Demakova & Shustova, 2021), использованию педагогом социальных сетей в воспитании школьников (Vlasova, 2021) и др.…”
Section: образование и саморазвитие том 17 № 4 2022unclassified
“…Их не так много, как хотелось бы, но это статьи ведущих российских специалистов по воспитательной проблематике. Исследователи поднимают проблемы научно-методического обеспечения процесса воспитания в школе (Selivanova & Parfyonova, 2021), системного подхода к применению исследовательских методов в теории вопитания (Demakova & Shustova, 2021), использованию педагогом социальных сетей в воспитании школьников (Vlasova, 2021) и др.…”
Section: образование и саморазвитие том 17 № 4 2022unclassified
“…Especially during the COVID-19 pandemic, universities were forced to offer online courses (Adedoyin & Soykan, 2023;Pokhrel & Chhetri, 2021) and make social interactions and share with their students so that students could communicate and connect with their students through social media platforms (Obi-Ani et al, 2020). Specifically, instructors and students have begun to use mostly these platforms since the beginning of the COVID-19 pandemic to share course content and create online course discussion groups to encourage them to discuss, learn, and teach courses (Vlasova, 2021). For example, a recent study of 1,720 medical students in Saudi Arabia by Alfaris et al (2018) found that 98% of participants indicated using SNS.…”
Section: Introductionmentioning
confidence: 99%
“…There are not as many of them as we would like, but these are articles by leading Russian experts on upbringing issues. Researchers raise the problems of scientific and methodological support of the process of education at school (Selivanova & Parfyonova, 2021), a systematic approach to the use of research methods in the theory of upbringing (Demakova & Shustova, 2021), the use of social networks by a teacher in the education of schoolchildren (Vlasova, 2021), etc.…”
mentioning
confidence: 99%